2012
DOI: 10.1175/wcas-d-11-00025.1
|View full text |Cite
|
Sign up to set email alerts
|

Boater Safety: Communicating Weather Forecast Information to High-Stakes End Users

Abstract: Recreational boaters in the Pacific Northwest understand that there is uncertainty inherent in deterministic forecasts as well as some of the factors that increase uncertainty. This was determined in an online survey of 166 boaters in the Puget Sound area. Understanding was probed using questions that asked respondents what they expected to observe when given a deterministic forecast with a specified lead time, for a particular weather parameter, during a particular time of year. It was also probed by asking r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 13 publications
1
22
0
1
Order By: Relevance
“…Several studies (Morss et al ., , ; Lazo et al ., ; Joslyn and Savelli, ; Savelli and Joslyn, ; Peachey et al ., ) show that most people are inclined to assign a certain range of uncertainty to a single‐value forecast provided by a deterministic model: uncertainty is anticipated by the user even when such information is not intentionally supplied.…”
Section: Resultsmentioning
confidence: 98%
“…Several studies (Morss et al ., , ; Lazo et al ., ; Joslyn and Savelli, ; Savelli and Joslyn, ; Peachey et al ., ) show that most people are inclined to assign a certain range of uncertainty to a single‐value forecast provided by a deterministic model: uncertainty is anticipated by the user even when such information is not intentionally supplied.…”
Section: Resultsmentioning
confidence: 98%
“…People realize that weather forecasts involve uncertainty even when they are presented as deterministic and attempt to estimate the uncertainty themselves . Indeed, everyday users anticipate a wide range of values for deterministic forecasts and a high FA rate for weather warnings, and they regard extreme forecasts as exaggerations . As a result of these intuitions, people may actually underestimate the risk in some situations if a valid uncertainty estimate is not provided.…”
Section: Introductionmentioning
confidence: 99%
“…Expressing the uncertainty in forecasts can be useful to experienced users of weather information, helping to improve decision‐making based on those forecasts (Nadav‐Greenberg and Joslyn, ; Joslyn and LeClerc, ). For example, Savelli and Joslyn () found that boaters in the Puget Sound area of Washington State may benefit from calibrated forecasts of uncertainty because they are then able to make their own assessment of risk, based on boat size.…”
mentioning
confidence: 99%